Exercise modality effect on VO2 off-transient kinetics at VO2max intensity - Sousa, A.; Rodriguez, F. A.; Machado, L.; Vilas-Boas, J. P.; Fernandes, R. J. (Experimental Physiology, 2015)
The kinetics of oxygen uptake (VO2 ) during recovery (off-transient kinetics) to different exercise modes is largely unexplored, hampering the prescription of training/ recovery to enhance performance. The purpose of this study was to compare the VO2 off-transient kinetics response between swimmers, rowers, runners and cyclists, during their specific mode of exercise at 100% of maximal oxygen uptake (VO2max ) intensity examining also the on/off symmetry. Four groups of 8 swimmers, 8 rowers, 8 runners and 8 cyclists performed (i) an incremental protocol exercise to assess the velocity or power associated to VO2max (vVO2max or wVO2max , respectively) and (ii) a square-wave transition exercise from rest to vVO2max /wVO2max until volitional exhaustion. Pulmonary exchange parameters were measured using a telemetric portable gas analyser (K4b(2) , Cosmed, Rome, Italy) and the on- and off-transient kinetics were analysed through a double exponential approach. For all exercise modes both transient periods were symmetrical in shape once they were both adequately fitted by a double exponential model. However, differences were found in the off-kinetic parameters between exercise modes: the amplitude of the fast-component VO2 off-response was higher in running compared with cycling (48 ± 5 and 36 ± 7 ml.kg(-1) .min(-1) , P<0.001, respectively) and the time constant of the same phase was higher in swimming compared with rowing and cycling (63 ± 5, 56 ± 5 and 55 ± 3 s, P<0.001, respectively). Although both phases were well described by a double exponential model, the differences between exercise modes had a potential effect and contributed to distinct VO2 off-transient kinetic patterns at 100% of VO2max intensity Exercise modality effect on VO2 off-transient kinetics at VO2max intensity. Available from: https://www.researchgate.net/publication/274731281_Exercise_modality_effect_on_VO2_off-transient_kinetics_at_VO2max_intensity